Research on the Vibration Response of High-Rise Buildings under Blasting Load - Yubao Yuan; Zhenghua Gao; Lu He; Zhen Lei (Mathematics)
The vibration caused by blasting load may result in damage to high-rise buildings. In view of this consideration, an investigation of the vibration law was conducted in the context of an actual engineering project. The objective of this study was to analyze the peak particle velocity (PPV), vibration frequency, and peak particle stress (PPS) of the buildings within a range of 50 m to 250 m from the epicenter, under the condition of a single-shot charge of 30 kg. To achieve this, a combination of theoretical analysis, field tests, and numerical experiments was employed. Sadovsky’s formula was used in combination with the least squares method to fit the propagation law of ground PPV. ANSYS 17.0/LS-DYNA and Origin 8.0 software were applied to study the amplification effect of building PPV and the relationship between PPV and PPS. Taking into account the difference between the height of the ground measuring point and the height of the explosive center, we investigated the PPV of high-rise buildings under three conditions of 36 m, 6 m, and −24 m drop from the explosive center, to strengthen the in-depth understanding of resonance effect. The following conclusions were reached: the ground PPV decreases with increasing horizontal distance from the explosive center, with the radial PPV being the largest. The vertical PPV of buildings exhibits a height amplification effect, with a magnification factor of 2.66. The radial and tangential PPVs of buildings demonstrate that the middle layer exhibits a relatively modest speed, whereas the low and high layers demonstrate considerably higher speeds. The greater the vertical distance from the explosion center is, the greater is the PPV. The vibration frequency is irregular, with an average of 10 Hz. The PPV of buildings is not proportional to the PPS, which is the highest at the bottom. It is recommended that the PPS of buildings be included in the criteria for safety allowances in blasting vibration.